Opinions and Discussions Claiming Around the Safivids (Journal of Alevism-Bektashism Studies, 2023)
The Safavids, the precursors of the Kızılbaş-Alevi tradition, have maintained their influence in our country and around the world, both in terms of their historical identity and philosophy. The Safavids have played a significant role over the Kızılbaş-Alevi communities living in Iran, Azerbaijan, northern Syria, Anatolia, and the Balkans from the beginning of the 14th century until today. However, many discussions regarding various aspects of the Safavids in the literature have yet to reach a definitive conclusion. Therefore, the debates surrounding the lives, works, and ideas of the Safavid Sheikhs and Shahs should be reexamined, the answers to the question “Who are the Safavids?” should be reconsidered, and new studies reflecting different perspectives on Kızılbaş-Alevism should be conducted. The aim of this article is to discuss the issue of the Safavid genealogy (nesebname), which is among the most debated topics concerning the Edebil Tekke, its Sheikhs, and the Safavid Shahs, by utilizing Safavid literature as a source. Additionally, the family’s religious affiliation (Shi’a, Sunni, Shafi’i) and the politicization of the order have made the issue of lineage significant among the Safavids. The attribution of Safavid lineage to four different ethnic origins, namely Seyyid/Arab, Fars/Ajam, Turk, and Kurd, has further increased interest in the subject. Given the existing literature and discussions, it will be emphasized that the relationship between the Kızılbaş-Alevi belief system, created by the Safavids, and the Turkish identity has not been adequately addressed in the literature. It will be highlighted that studies prepared from this perspective are necessary to understand the ideas developed by the Safavid Sheikhs and Shahs and the communities (Kızılbaş-Alevis) living in accordance with these ideas.